A bioinspired hollow g-C3N4–CuPc heterostructure with remarkable SERS enhancement and photosynthesis-mimicking properties for theranostic applications. Issue 22 (19th May 2022) - Su, Yu; Yuan, Baozhen; Jiang, Yaowen; Wu, Ping; Huang, Xiaolin; Zhu, Jun-Jie; Jiang, Li-Ping
Abstract : Thylakoid-inspired HCNs@CuPc@HA is designed as a light-harvesting nanocomposite and photosynthesis-mimicking nanoscaffold to simultaneously enhance chemical mechanism-based SERS and photosynthesis-mimicking catalysis for theranostics application. Abstract : Surface-enhanced Raman scattering (SERS) based on chemical mechanism (CM) has great potential for superior stability and selectivity. Moreover, a bioinspired CM-Raman substrate-Raman reporter system with charge separation and electron transport nature provides thylakoid-mimicking potential for multifunctional applications. Herein, hollow carbon nitride nanospheres hierarchically assembled with a well-oriented copper(ii ) phthalocyanine layer and hyaluronic acid (HCNs@CuPc@HA) were designed as a light-harvesting nanocomposite and photosynthesis-mimicking nanoscaffold that enhance both CM-SERS and photoredox catalysis. Remarkable SERS enhancement was achieved due to the strengthened short-range substrate–molecule interaction, enriched CuPc molecule loading and enhanced light–mater interactions. Meanwhile, the uniform CuPc molecule film mimics a photo-pigment to accelerate the near infrared (NIR)-oxygen generation and photodynamic catalysis of photosynthetic membrane-like HCNs. The experimental findings were further validated by numerical theory analysis. The greatly enhanced SERS signal and photosynthetic-mimicking properties of the heterostructure (denoted as HCNCHs) were successfully employed for circulating tumor cell (CTC) diagnosis and SERS imaging-guided cancer catalytic therapy in tumor xenograft models.